Anti-NMDA receptor encephalitis: a literature review (Research, Society and Development, 2023)
Introduction: Autoimmune encephalitis is related to a group of inflammatory diseases of the central nervous system, being a class in which there is production of antibodies against autoantigens. Viral neuroinfections are known triggers for anti-NMDA receptor encephalitis. Objective: the present work aims to present a better understanding of the pathology in question. Method: Refers to a literature review, using the databases: PubMed and Scielo as search engines. Works in English, Portuguese and Spanish, complete and related to the main theme, were included. Incomplete works, in other languages and that discussed encephalitis exclusively due to tumor causes were excluded. In total, 77 articles made up the analytical corpus of the research. Results and Discussion: Viral neuroinfections are among the main etiologies for anti-NMDA receptor encephalitis. It classically affects young women with an acute or subacute presentation of psychiatric symptoms, epilepsy, cognitive impairment, lowered level of consciousness, and autonomic dysfunction. The diagnosis is based on clinical criteria and laboratory tests. Initial treatment consists of the use of corticosteroids. It has a good prognosis when therapeutic measures are started early. Conclusion: With a variable clinical presentation, this pathology presents itself as a diagnostic challenge. New studies elucidating the pathophysiology related to anti-NMDA receptor encephalitis caused by viral infections are needed.